New conjugate gradient methods for solving large-scale unconstrained optimization problems - Mohd Rivaie Mohd Ali (Terengganu: Universiti Malaysia Terengganu, 2014)
Conjugate gradient methods hold an important role in unconstrained optimizations. Numerous recent studies and modifications have been aimed to improve these methods. In this research, four modifications of the conjugate gradient coefficient (Bk ) are proposed in order to solve unconstrained optimization problems using exact line searches.